Rare Earth Element concentrations of bulk sediment leachates at DSDP Site 72-517, Rio Grande Rise - Oluwaseun Soaga; Ed C Hathorne; Martin Frank; Polina Tselykh; Lena Jebasinski; Dirk Nürnberg (PANGAEA, 2025)
This dataset includes the analysis of sediment core DSDP 517 (30°56.81 extquotesingleS, 38°02.47 extquotesingleW, 2963 m water depth) recovered from the Rio Grande Rise within the modern day North Atlantic Deep Water (NADW). This dataset contains Rare Earth Element (REE) concentrations measured on bulk sediment leachates of DSDP 517. The dataset also includes measured reference materials USGS BCR-1, USGS AGV-2, USGS MAG-1. Measurements were made on an Agilent 7500ce ICP-MS.
In: Soaga, O et al. (2025): Radiogenic Neodymium isotope and REE concentrations of authigenic and detrital phases and benthic foraminiferal stable oxygen and carbon isotopes at DSDP Site 72-517, Rio Grande Rise [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974490